1995
DOI: 10.1002/mds.870100513
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of cervical dystonia (spasmodic torticollis) in Rochester, Minnesota

Abstract: The natural history of cervical dystonia (spasmodic torticollis) was investigated in a population-based study in Rochester, Minnesota. Eleven new cases were identified with onset during the 20-year period 1960-1979. The overall incidence rate was 1.2 per 100,000 person-years (95% confidence interval 0.5-1.9) with a female:male ratio of age-adjusted incidence rates of 3.6:1. A unitary etiology was not apparent: injury antedated onset in four of the 11 patients, whereas six had documented thyroid disease and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
2
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 22 publications
(6 reference statements)
2
40
2
1
Order By: Relevance
“…Similar results have been reported for other forms of CD [2]. However, no female gender preference was reported in our cohort [11]. Although we report a somewhat lower frequency of RC than previous studies [4], this may reflect local referral patterns and/or use of alternative criteria for RC.…”
Section: Discussioncontrasting
confidence: 46%
“…Similar results have been reported for other forms of CD [2]. However, no female gender preference was reported in our cohort [11]. Although we report a somewhat lower frequency of RC than previous studies [4], this may reflect local referral patterns and/or use of alternative criteria for RC.…”
Section: Discussioncontrasting
confidence: 46%
“…[1][2][3][4][5][6] There have been two previous estimates of the incidence of this disorder, and both were performed in populations of largely European descent. 7,8 There are no published estimates from ethnically diverse populations. Studies from Japan have variably suggested a lower overall prevalence of focal dystonias than in European populations 9 and a different pattern of relative prevalence among the focal dystonias.…”
mentioning
confidence: 98%
“…Dystonia is often initiated or worsened by voluntary action and associated with overflow muscle activation 1 . Among the various forms of dystonia, the most frequent in adults is the cervical dystonia (CD), a focal type that affects the muscles of the cervical region 2 .…”
mentioning
confidence: 99%